Analysis of Fire Alarm Performance Effectiveness in MV. Rajakarta: Analisis Efektivitas Kinerja Alarm Kebakaran di KMP. Rajakarta - Sinaga, Meidiana Putri; Wiweko, Albert; Siregar, Muhammad Sapril (PT. Alpha Trianguli Australis, 2024)
Fires on ships pose a high risk due to limited access to help from land and firefighting equipment. To minimize these risks, it's important to maximize the effectiveness of the fire alarm system. This can be done by quickly detecting any smoke or fire using the alarm system and taking immediate action before the fire spreads. A qualitative descriptive method was used in this research to investigate the decline in the working function of fire alarms. The research focused on the problems with fire alarm smoke detectors and the correct maintenance methods. The findings of the research indicate that the lack of maintenance and repair of the fire alarm system are the main factors that cause the decline in the capability of fire alarm sensors. To ensure that the fire alarm system works properly, it should be routinely and periodically maintained. This will help to prevent any potential issues and ensure that the alarm system is always functioning at its best.